المبيدات الكميائية - بن عمارة, سناء (university of el oued/جامعة الوادي, 2013)
تعتبر المبيدات الكيميائية أحد ملوثات البيئة فهي تتيتمدف في مكاف ية الآفيات الزراعيية في الميزار وال قول، و كذلك حشيرات المايا ل الااةلية اميران ان تيا و ال ييوا . و بيالرم ميف فعاليية يذم المبييدات الكيميائييية و ميزاتهييا اتةتدييا ة، فقييد رهيير اييرر ا عليين ايي ة ان تييا و ال يييوا و رهييرت العد ييد مييف ااجااس المقاومة لها، باناافة إلن إبا ة ال شرات الاافعة. و تشير العد د مف الدراسات العالمية إلن أخطار المبيدات و ارورة ترشيد استمدامها لميا تتيببم ميف حاتت تتم حا و مزمف للإ تا و ال يوا و الت أ ت و ت تزال تؤ ي إلن تشو ات و سرطا ات ووفييات حدثت و ت دث مف جراء اتستمداف العشوائ للمبيداتChemical pesticides one of the pollutants of the environment, they used in agricultural pest control in farms and fields, as well as homes insects; the transporter for human and animal diseases. Although the effectiveness of these chemical pesticides and the economic advantages has shown harmfulness on human and animal health, and has appeared many races have resistance, in addition; the extermination of beneficial insects. Many universal studies mention that about the dangerous of pesticides and the necessity to rationalization uses, for what they caused chronic ills and acute toxicity to humans and animals, which have leading for the malformations, cancers and deaths that was as a result of the pesticides indiscriminate uses.
ليسانس كيمياء
Keywords: المبيدات، ملوث البيئة، ا ة ان تا ، سوء اتستمداف; pesticides, environment pollutant, human health, indiscriminate uses.